Enhancement of HSA-pFSHβ production by disrupting YPS1 and supplementing N-acetyl-L-cysteine in Pichia pastoris - Luo, Gang; Geng, Zijian; Kuerban, Buayisham; Xu, Yingqing; Yang, Jingjing; Liu, Jiying; Li, Muwang (Frontiers in Microbiology, 2022)
Introduction Pichia pastoris is widely used for the production of recombinant proteins, but the low production efficiency hinders its wide application in biopharmaceuticals. Moreover, many biopharmaceutical-like proteins are accompanied by degradation during secretory expression in P. pastoris. Objective In this study, we used human serum albumin and porcine follicle-stimulating hormone β (HSA-pFSHβ) fusion protein as a model protein to investigate whether YPS1 and YPT7 gene disruption and N-acetyl-L-cysteine (NAC) supplementation have synergistic effects to inhibit the degradation of recombinant proteins. Results and discussion Our results showed that YPS1 gene disruption reduced the degradation of intact HSA-pFSHβ and increased the yield of intact protein in the culture medium and cells without affecting the integrity of the cell wall. Moreover, the beneficial effects of YPS1 gene disruption were associated with the upregulation of the MAPK signaling pathway and maintenance of redox homeostasis. YPS1 gene disruption and NAC supplementation had synergistic effects on HSA-pFSHβ production. In addition, disruption of vacuolar morphology by YPT7 gene disruption or NH4Cl treatment affected the production of recombinant HSA-pFSHβ protein. Furthermore, YPT7 gene disruption inhibited the processing of signal peptide in high-level produced HSA-pFSHβ strain. In conclusion, our results demonstrated that YPS1 disruption could reduce the degradation of intact HSA-pFSHβ proteins, and synergistically increase the yield of intact HSA-pFSHβ with NAC supplementation. This study provided a valuable reference for reducing recombinant protein degradation and therefore improving the yield of recombinant proteins in P. pastoris.